Analysis of Green HRM, Green Value Strategic Improving CSR and Green Performance in Central Kalimantan HSL Palm Companies - Mering, Laden (International Review of Management and Marketing, 2024)
Research in the field of human resources that raises the topic of Green HRM to improve Green Performance. The research base also assesses the role of Strategic Green Value in encouraging corporate CSR and has an impact on increasing green performance. Research was conducted quantitatively on 100 CSR respondents from Sustainable Hutan Sawit Lestari palm oil companies in Central Kalimantan. The results of the analysis with Smart PLS show that Green HRM is significant in increasing Green Performance by (5%, but not significantly increasing the CSR program. The next significant result is Green Value Strategy on Green Performance and the significant effect of increasing CSR by 63%. The results of the analysis of the mediating role are a combination namely the CSR program has a significant positive influence on the relationship between Green Value Strategy and Green Performance and there are insignificant results regarding the mediating role of CSR on the relationship between Green HRM in improving Green Performance. Overall the research model from the Q square value shows 95%, namely the importance of Green HRM, Green Value Strategy, CSR in Green Performance. Implementation of these results can be applied to Sustainable Hutan Sawit Lestari companies for managing HRM and natural resources by providing skills training in maintaining the quality of life of the organization and the company environment in a CSR program to improve the company’s reputation. In further research you can consider Green Technology.